Abdominal Aortocaval Vascular Injury following Routine Lumbar Discectomy. (7th October 2014) - Leech, Matthew; Whitehouse, Marc James; Kontautaite, Ruta; Sharma, Mukesh; Shanbhag, Sumant
Abstract : Vascular complications following spinal surgery are potentially fatal; however, fortunately they are rare. This risk is often focused on the close proximity of the surgical field to retroperitoneal structures. Prompt diagnosis is essential; however, bleeding is often occult, and this may therefore delay management of this condition. Despite previous reports many clinicians may not be aware of this potentially fatal complication. The overall morbidity and mortality may be reduced by prompt diagnosis and treatment. Clinicians must, therefore, have a high degree of suspicion in all patients who undergo spinal surgery. We therefore present a case of a 51-year-old man who sustained an aortocaval injury during a revisional lumbar discectomy. The patient developed refractory hypotension, which deteriorated into PEA arrest. Emergency laparotomy was performed which revealed an aortocaval injury. Immediate primary vascular repair was successfully performed. The patient was resuscitated and made a full recovery.